Portfolio analysis of academic programmes in UiTM Pahang / Norlaila Abdullah - Abdullah, Norlaila (2007)
This paper analyses the various teaching programmes offered at Universiti Teknologi MARA (UiTM) Pahang to identify the least and most successful areas of teaching provisions and use the information to affect a strategy. Some benchmark criteria used in assessing each of the teaching programmes include employability of graduates, recruitment success, and relative student turnover and cost recovery performance. The courses are ranked accordingly that would ultimately serve as an input to strategic leaders' decision in ensuring that the teaching programmes are moving towards the achievement of its vision, mission and objectives.